Proceso de atención de enfermería en adolescente con asma bronquial. - Fuentes Alemán, Johanna Marlene (2021)
Bronchial asthma is a pathology that affects the respiratory tract, the bronchi, triggering inflammation in its walls, narrowing the lumen of these, thus making it difficult to breathe, causing coughing, pain when breathing and heaviness in the chest. Asthma is a non-communicable disease, which affects children and adults. It is estimated that by 2019, this pathology affected 263 million people and caused 465,000 deaths worldwide according to the World Health Organization (WHO). In Ecuador, it is estimated that around 7% of the population is suffering from this disease and only 5% have received timely treatment with the proper prevention and control measures. This clinical case study is based on a 10-year-old adolescent patient with bronchial asthma, who was admitted to the IESS Babahoyo General Hospital, where the objective of the nursing staff was to apply the nursing care process, taking into account the Symptoms, risk factors, clinical history, basic needs and altered functional patterns in the patient, in order to contribute to her speedy recovery. For the elaboration of this clinical case study, a nursing care process (PAE) is elaborated; which allowed the elaboration and application of interventions during the nursing practice, carrying it out in a scientific and orderly manner using the NANDA, NOC, NIC taxonomy, in order to obtain favorable results in terms of the patient's recovery.